2013
DOI: 10.1152/ajpregu.00073.2013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age on ACTH, corticosterone, glucose, insulin, and mRNA levels during intermittent hypoxia in the neonatal rat

Abstract: Chintamaneni K, Bruder ED, Raff H. Effects of age on ACTH, corticosterone, glucose, insulin, and mRNA levels during intermittent hypoxia in the neonatal rat. Am J Physiol Regul Integr Comp Physiol 304: R782-R789, 2013. First published March 13, 2013 doi:10.1152/ajpregu.00073.2013.-Apnea, the temporary cessation of respiratory airflow, is a common cause of intermittent hypoxia (IH) in premature infants. We hypothesized that IH elicits a stress response and alters glucose homeostasis in the neonatal rat. Rat p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 26 publications
3
39
0
Order By: Relevance
“…The IH protocol was based on a previously published model (9). Six cycles of IH were performed daily over approximately 60 minutes.…”
Section: Animal Treatment and Neonatal Ih Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…The IH protocol was based on a previously published model (9). Six cycles of IH were performed daily over approximately 60 minutes.…”
Section: Animal Treatment and Neonatal Ih Protocolmentioning
confidence: 99%
“…All analytic techniques have been previously published (9). Plasma ACTH and corticosterone were measured via RIA (MP Biomedicals).…”
Section: Hormone and Glucose Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, since the railway began service, .10 million travelers have visited the Tibet region in 2012, of whom 31% developed AMS despite traveling with an oxygen supply on the train (3). Increasing evidence in both humans and animals suggests that exposure to either high-altitude or hypobaric hypoxia influences plasma insulin levels and glucose homeostasis, depending on the oxygen level and duration of exposure (4)(5)(6)(7)(8)(9). We previously showed that subacute hypoxia at an altitude of 5,000 m for 5 days reduces plasma insulin in rats, and this effect is blocked by a corticotropin-releasing hormone (CRH) receptor 1 (CRHR1) antagonist in vivo (10).…”
mentioning
confidence: 99%
“…Conditions that cause stress to the infant increase the risk of hyperglycemia due to increased secretion of counter-regulatory hormones [19]. Among many stress factors, intermittent hypoxia is known to elicit an important adrenal response and significantly alters glucose homeostasis [20]. In our patient, fetal suffering during premature delivery due to placental abruption and respiratory distress requiring mechanical ventilation could have induced a stress response sufficient to increase insulin needs above the threshold met by β-cells with the HNF4A variant.…”
Section: Discussionmentioning
confidence: 99%